Nilai Hak Asasi Manusia dalam Penegakan Hukum terhadap Anak Pelaku Tindak Pidana - Sukardi; Q. Zaman, MSI (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research aims to examine the implementation of human rights (HAM) protection for children who commit criminal acts in the law enforcement system in Indonesia. The research problem is how to protect the human rights of children who commit criminal acts in the law enforcement system in Indonesia. The research method uses qualitative normative legal research by analyzing legal doctrine and related laws and regulations. The research method used is qualitative normative legal research, namely reviewing various statutory regulations and related literature to understand legal rules and their implementation in the field. The research results show that from a juridical-normative perspective, the protection of children's human rights is regulated in various national and international laws and regulations. However, there are several challenges in implementing it in the field, such as limited understanding of legal authority, facilities and implementing regulations. For this reason, it is necessary to strengthen socialization, legal framework and implementation facilities, as well as continuous evaluation in order to realize universal protection of children's human rights.